IMPROVING STUDENT’S WRITING ABILITY IN NARRATIVE TEXT BY USING CHRONOLOGICAL 3D PICTURES AS MEDIA (ELT Forum: Journal of English Language Teaching, 2013)
The use of chronological 3D pictures in this study has a purpose at developing students’ competence in writing narrative texts. The objective of the study is to find out the student’s difficulties in writing narrative text, how effective chronological 3D pictures improve student’s ability in writing narrative, and why chronological 3D pictures proposed as media in teaching narrative text. Four tests given to the students showed student’s improvement. The mean of the pre-test was 63.12. Cycle 1’result was 69.25 and cycle 2 ‘result was 77.37. After that, the mean of the post-test was 86.25. From the result, it can be seen that chronological 3D pictures gave significance improvement in teaching narrative text for tenth grade students. In line with the result, I propose that using chronological 3D picture as a media to improve student’s writing narrative text can be one of the positive ways to increase students’ enthusiasm in learning English.